Reaksi Pasar Modal Indonesia Sebelum Dan Selama Masa Invasi Rusia Ke Ukraina Terhadap Harga Saham Pada Perusahaan Energi Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Safitri, Fynna Alvionita; Fatmawati, Elsye (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to analyze the effect of the Russian Invasion of Ukraine on the stock prices of companies in the energy sector listed on the Indonesia Stock Exchange before and during the Russian Invasion of Ukraine. The type of research used is quantitative. The sample in this study amounted to 61 companies obtained by purposive sampling technique. Based on the results of hypothesis testing for each variable, it can be concluded that partially the Abnormal Return variable has a positive and insignificant effect on stock prices and there is a significant difference before and during the Russian Invasion of Ukraine, the Trading Volume Activity variable has a negative and insignificant effect on stock prices and there is a significant difference before and during the Russian Invasion of Ukraine, while the Market Capitalization variable has a significant positive effect on stock prices and there is no significant difference between before and during the Russian Invasion of Ukraine in energy sector companies listed on the IDX. The results of the R-Square determination test of the effect of the Abnormal Return, Trading Volume Activity, Market Capitalization variables on Stock Price are 41.19% and the remaining 58.81% is influenced by other factors not included in the regression model.